Wen ben, di yu yu jie shi de xin shi jiao : Zhongguo Dongbei di qu de Jidu zong jiao yu Zhong xi wen hua jiao liu (Qing chu zhi Minguo) - Zhao, Yifeng, 1953- (Shanghai : Shanghai ren min chu ban she, 2013)
Summary in vernacular field only.
Includes bibliographical references.
Abstracts also in English.
Keywords: Manchuria (China) -- Church history; Manchuria (China) -- Civilization -- Christian influences